Population Dynamics of Long-tailed Ducks Breeding on the Yukon-Kuskokwim Delta, Alaska - Schamber, Jason L.; Flint, Paul L.; Grand, J. Barry; Wilson, Heather M.; Morse, Julie A. (ARCTIC, 2009)
Population estimates for long-tailed ducks in North America have declined by nearly 50% over the past 30 years. Life history and population dynamics of this species are difficult to ascertain, because the birds nest at low densities across a broad range of habitat types. Between 1991 and 2004, we collected information on productivity and survival of long-tailed ducks at three locations on the Yukon-Kuskokwim Delta. Clutch size averaged 7.1 eggs, and nesting success averaged 30%. Duckling survival to 30 days old averaged 10% but was highly variable among years, ranging from 0% to 25%. Apparent annual survival of adult females based on mark-recapture of nesting females was estimated at 74%. We combined these estimates of survival and productivity into a matrix-based population model, which predicted an annual population decline of 19%. Elasticities indicated that population growth rate (?) was most sensitive to changes in adult female survival. Further, the relatively high sensitivity of ? to duckling survival suggests that low duckling survival may be a bottleneck to productivity in some years. These data represent the first attempt to synthesize a population model for this species. Although our analyses were hampered by the small sample sizes inherent in studying a dispersed nesting species, our model provides a basis for management actions and can be enhanced as additional data become available. Les estimations de populations d’hareldes kakawis en Amérique du Nord ont chuté de près de 50 pour cent ces 30 dernières années. Le cycle biologique et la dynamique des populations de cette espèce sont difficiles à établir car ces oiseaux nichent moyennant de faibles densités dans une vaste gamme d’habitats. De 1991 à 2004, nous avons recueilli des données sur la productivité et la survie des hareldes kakawis à trois emplacements du delta Yukon-Kuskokwim. Les couvées atteignaient 7,1 oeufs en moyenne, tandis que le succès de reproduction s’établissait généralement à 30 pour cent. En moyenne, 10 pour cent des jeunes ...